Work History and the Access to Contributory Pensions in Uruguay : Some Facts and Policy Options - Bucheli, Marisa (World Bank, Washington, DC, 2014)
Incomplete and highly fragmented work histories threaten to leave many contributors of the pension schemes in Latin America without the minimum pension guarantee or even without access to the ordinary pension. We propose a methodology to assess this risk, identify vulnerable groups and study potential determinants of the history of contributions using information from the work history records of the social security institutions. We apply this methodology to the largest social security institution of Uruguay, the Banco de Previsión Social, and show that the majority of contributors to this institution might not comply with the minimum number of years of contribution that is currently required to access an ordinary pension when they reach the retirement age.